2006
DOI: 10.1073/pnas.0603552103
|View full text |Cite
|
Sign up to set email alerts
|

Identification of aHoxc8-regulated transcriptional network in mouse embryo fibroblast cells

Abstract: The transcription factor, Hoxc8, is a member of the homeobox gene family that is vital for growth and differentiation. Previously, we identified 34 genes whose expression levels were changed at least 2-fold by forced expression of Hoxc8 in C57BL͞6J mouse embryo fibroblast cells using a mouse 16,463-gene oligonucleotide microarray. In the present study, we used the combined power of microarray profiling, global Hoxc8 DNA-binding site analysis, and high-throughput chromatin immunoprecipitation assays to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 39 publications
3
46
1
Order By: Relevance
“…6 One of those HOX transcription factors-HOX-C8-raised our attention as it was shown to regulate the expression of several target genes implicated in processes with relevance to tumorigenesis. [16][17][18] To elucidate if HOX-C8 is also a target for miR-196a in melanoma cells, we first determined HOX-C8 mRNA expression levels in our cell panel and found strongly enhanced expression (ranging from two-fold to about 18-fold) in the melanoma cell lines compared with NHEMs (Fig. 1b).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…6 One of those HOX transcription factors-HOX-C8-raised our attention as it was shown to regulate the expression of several target genes implicated in processes with relevance to tumorigenesis. [16][17][18] To elucidate if HOX-C8 is also a target for miR-196a in melanoma cells, we first determined HOX-C8 mRNA expression levels in our cell panel and found strongly enhanced expression (ranging from two-fold to about 18-fold) in the melanoma cell lines compared with NHEMs (Fig. 1b).…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose, we selected a set of four genes-osteopontin, cadherin-11, calponin-1 and hugl-1-out of the HOX-C8 target genes described in literature. [16][17][18] We first determined mRNA expression levels of those genes in our panel of stable cell clones. We were able to detect significantly reduced Osteopontin mRNA levels (by about 50%; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was accepted that Hox genes could regulate the promoter of genes by binding consensus elements TTAT, TAAT and TTAC. Combined with microarray profiling, DNA binding site analysis and chromatin immunoprecipitation (Chip) analysis identified that five genes are directly regulated by HoxC8 in mouse embryo fibroblast cells (27). These candidate genes have been implicated in oncogenesis, cell proliferation and cell apoptosis.…”
Section: Introductionmentioning
confidence: 99%